2022
DOI: 10.1080/17515831.2022.2083405
|View full text |Cite
|
Sign up to set email alerts
|

Sliding wear performance of TiAl-based nitride coatings deposited on ADI by cathodic arc deposition and plasma based ion implantation and deposition

Abstract: This work studied the sliding wear performance of TiAl-based nitride coatings synthesized on austempered ductile iron (ADI) by cathodic arc deposition (CAD) and plasma-based ion implantation and deposition (PBIID). Monolayer CAD TiAlN films and bilayer CAD and PBIID TiAl/TiAlN films deposited on an experimental device were analyzed and benchmarked against a commercial bilayer CAD film. Sliding wear was evaluated in a pin-on-disc tribometer. Two test conditions were employed, one intended to prevent damage (low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Surface lubricity, coefficient of friction, microhardness and elastic modulus were improved by controlling the carbon content. Colombo et al [22] reported that TiAlN-coated iron samples displayed steady-state friction coefficients between 0.2 and 0.6 lower than that of the uncoated samples. Larsson et al [23] studied the mechanism of coating failure in TiN-coated steel.…”
Section: Introductionmentioning
confidence: 99%
“…Surface lubricity, coefficient of friction, microhardness and elastic modulus were improved by controlling the carbon content. Colombo et al [22] reported that TiAlN-coated iron samples displayed steady-state friction coefficients between 0.2 and 0.6 lower than that of the uncoated samples. Larsson et al [23] studied the mechanism of coating failure in TiN-coated steel.…”
Section: Introductionmentioning
confidence: 99%